PEMODELAN REGRESI SPASIAL PADA ANGKA PARTISIPASI MURNI JENJANG PENDIDIKAN SMA SEDERAJAT DI PROVINSI KALIMANTAN SELATAN - Suci Anshari; Dewi Sri Susanti; Fuad Muhajirin Farid (RAGAM: Journal of Statistics & Its Application, 2022)
This research is done for modeling of the Pure Enrolment Rate (PER) at the senior high school level in South Kalimantan Province that uses analysis of spatial regression. The purpose of this analysis is to construct the modeling of spatial regression of the Pure Enrolment Rate (PER) at the senior high school level in South Kalimantan Province and to identify the significant factors that influent the pure enrollment rate (PER). The result of this research shows that the modeling of spasial regression is suitable for use in the Pure Enrolment Rate (PER) at the senior high school level in South Kalimantan Province in 2017 – 2019 is the Spatial Autoregressive Model (SAR). The model form can be seen that in 2017 there is no significant influence factors to the PER, in 2018 the ratio of the student number to the school number (X5) and the ratio of the student number to the teacher number (X6) that are the influence factors significantly to the Pure Enrollment Rate (PER), while in 2019 only the factor of the ratio of the students number to the schools number (X5 ) that influents significantly to the PER.Keywords:   PER, Education, and Spatial Regression Analysis